Overall Water Splitting: Cobalt Phosphides Nanocrystals Encapsulated by P‐Doped Carbon and Married with P‐Doped Graphene for Overall Water Splitting (Small 10/2019). Issue 10 (8th March 2019) - Yang, Jing; Guo, Donghua; Zhao, Shulin; Lin, Yue; Yang, Rui; Xu, Dongdong; Shi, Naien; Zhang, Xiaoshu; Lu, Lingzhi; Lan, Ya‐Qian; Bao, Jianchun; Han, Min
Abstract : Utilizing pre‐synthesized supramolecular gels and a controllable thermal conversion technique, Yue Lin, Min Han, and co‐workers prepare three kinds of cobalt phosphides nanocrystals encapsulated by P‐doped carbon (PC) and "married" with P‐doped graphene (PG) nanohybrids. Compared with their pure phase counterparts, the mixed‐phase nanohybrids manifest better electrocatalytic performance toward overall water splitting (OWS). This work sheds light on the optimization of transition metal phosphides nanostructures based on phase engineering, and promotes their applications in OWS or other renewable energy options.